Functional Analysis of the Erwinia herbicola tutB Gene and Its Product - Katayama, Takane (American Society for Microbiology, 2002)
The tutB gene, which lies just downstream of tpl, has been cloned from Erwinia herbicola, and its product was analyzed. Despite its high sequence similarity to tryptophan transporters, TutB was found to be a tyrosine-specific transporter. Tryptophan acted as a competitive inhibitor of tyrosine transport. Unlike the tryptophanase operon, the tpl and tutB genes do not constitute an operon.